Sarcosine as an add-on treatment to antipsychotic medication for people with schizophrenia: a systematic review and meta-analysis of randomized controlled trials. (3rd April 2021) - Marchi, Mattia; Galli, Giacomo; Magarini, Federica Maria; Mattei, Giorgio; Galeazzi, Gian Maria
ABSTRACT: Background : N-methyl-glycine (sarcosine) may improve symptoms of schizophrenia via NMDA-receptor modulation. We undertook a systematic review and meta-analysis to determine the short- and long-term effectiveness of sarcosine for schizophrenia. Research design and methods : The databases Medline, Scopus, EMBASE, Cochrane Library, and PsycINFO were searched. We included six independent randomized controlled trials of sarcosine as add-on treatment to current antipsychotic medication, involving 234 adult participants with schizophrenia, and reporting data on symptom severity. Standardized mean differences (SMDs) were used to assess continuous outcomes. Results : In all of the trials, sarcosine was administered orally at 2 g/day. Treatment with sarcosine did not show a significant effect size at any of the pre-established time points (2, 4, 6, or >6 weeks), due to marked quantitative heterogeneity. However, sarcosine was associated with significant reductions of symptom severity in the subgroups of people with chronic schizophrenia and no treatment resistance (namely, without added-on clozapine) in relation to the SMD after 6 weeks treatment at −0.36 and −0.31, respectively. Conclusions : People with chronic and non-refractory schizophrenia may benefit from the use of sarcosine as an add-on treatment to antipsychotic medication. Due to the good tolerability of this compound, future trials with larger sample sizes appear worthwhile.